Prospect of research hotspots in prevention and treatment of diseases based on intestinal microbiome - Cai, Yue; Zhang, Yuting; Wang, Wenxue; Geng, Jiawei (Frontiers in Immunology, 2022)
With the in-depth study of gut microbiota, the methods of preventing and treating diseases have gradually diversified. But there is still lack of precise therapies methods to better treat the diseases. Therefore, researcher must focus on how to accurately regulate gut microbiota to achieve it. In order to promote the rapid development of this field, we provide several insights in gut microbiome-based precision therapies while prospecting the future directions.